2020
DOI: 10.1038/s41598-020-58735-8
|View full text |Cite
|
Sign up to set email alerts
|

In utero elemental tags in vertebrae of the scalloped hammerhead shark Sphyrna lewini reveal migration patterns of pregnant females

Abstract: Vertebral microchemistry recently allowed to infer the migration patterns of the scalloped hammerhead shark Sphyrna lewini in the Mexican Pacific, however conclusions regarding the movements of reproductive females were hindered by the small sample size. Considering that S. lewini is a placental viviparous species, maternal supply of nutrients to the embryos might influence their vertebral microchemistry while in utero and provide intrinsic markers of the pregnant female environmental histories. This hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Maternal loading is the process by which pregnant females transfer elements and molecules to their embryos via lipid mobilization (Addison and Brodie, 1987). This process is known to occur in sharks with regard to trophically derived contaminants in liver and muscle tissue (Lyons et al, 2013;Mull et al, 2013), and trace elements in the vertebrae of shark embryos (Coiraton and Amezuca, 2020). Both Zn and Mn are thought to be primarily incorporated into elasmobranch vertebrae via dietary sources as opposed to ambient environmental conditions (Mathews and Fisher, 2009), so it is reasonably likely that these trophically derived elements would undergo maternal loading during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal loading is the process by which pregnant females transfer elements and molecules to their embryos via lipid mobilization (Addison and Brodie, 1987). This process is known to occur in sharks with regard to trophically derived contaminants in liver and muscle tissue (Lyons et al, 2013;Mull et al, 2013), and trace elements in the vertebrae of shark embryos (Coiraton and Amezuca, 2020). Both Zn and Mn are thought to be primarily incorporated into elasmobranch vertebrae via dietary sources as opposed to ambient environmental conditions (Mathews and Fisher, 2009), so it is reasonably likely that these trophically derived elements would undergo maternal loading during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of maternal regions of White Shark vertebrae suggest that mothers of three subadults collected in the GC (GC13, GC14 and GC15) could have been in the GC for the duration of pregnancy, since Overall, Mg:Ca, Mn:Ca, and Zn:Ca tended to decrease through gestation which may relate to a switch from yolk to uterine milk nourishment during embryonic development (Sato et al, 2016;Tomita et al, 2022) as described above for SIA. Previous studies have suggested that maternal Sr:Ba and Pb:Ca might be indicators of offshore to nearshore movements in pregnant Scalloped Hammerhead Sharks (Coiraton and Amezcua, 2020), but our study on younger sharks evaluates migration over more regional scales, making comparisons difficult. Maternal offloading of both essential (Mn, Zn) and nonessential (Ba) elements between mother and offspring muscle and liver tissue has been reported in other shark species (de Souza-Araujo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados que aquí se presentan indican que actualmente la captura de H. longus pudiera no ser sustentable para el caso de esta pesquería, puesto que las capturas están representadas principalmente por organismos que no han alcanzado una etapa de madurez sexual, esta situación se repite a lo largo de su zona de distribución según lo evidenciado por distintos autores. Finalmente, debido al aumento en la presión pesquera y a que la información con respecto a las capturas de rayas es pobre (Ixquiac et al, 2009), es importante continuar realizando investigaciones y estudios que permitan promover y establecer estrategias de manejo para la conservación de este recurso (Coiraton & Amezcua, 2020).…”
Section: Discussionunclassified